Determinants of accurate visual perception of child anthropometric phenotype among ethnically diverse preschool parents in the United States. (8th June 2020) - Messiah, Sarah E.; Weerakoon, Sitara; Atem, Folefac; Schulte, Mikayla; Lebron, Cynthia; Kambali, Shweta; Mathew, Matthew Sunil; Chang, Catherina; Natale, Ruby A
Abstract: The literature reports that regardless of the high obesity prevalence estimates in young children, parents often do not accurately perceive their child's weight status. The purpose of this analysis was to examine the association between parent/child demographic characteristics including ethnicity, country of birth and years living in the United States and the perception of child's anthropometric phenotype status based on a visual silhouette instrument. Caregiver ( n  = 456) and child sociodemographic, perception of child anthropometric phenotype status and height/weight measurements were collected in 2015, from 24 childcare centres in Miami, Florida, among children ages 2‐to‐5 years old. Chi‐square analysis determined parent perception accuracy by actual child healthy (<body mass index [BMI] 85th percentile) or unhealthy (≥ BMI 85th percentile) status. Multivariable linear regression modelled phenotype trends by caregiver perception. Twenty‐eight per cent of the sample was of unhealthy weight. Overall, 74.6% of caregivers did not accurately identify their child's BMI phenotype category versus 25% who did ( p  < .001); 8% of Hispanic and 13% of non‐Hispanic parents of a child with an unhealthy BMI correctly identified their child's anthropometric phenotype. A higher proportion of Cuban (22%) caregivers of a child with an unhealthy BMI percentile versus Mexican caregivers (13.9%) visually identified their child as healthy weight. Child BMI percentile was significantly associated with parent perception of child healthy phenotype (OR: 1.05, 95% CI 1.04, 1.06). Findings here add evidence to the existing body of literature that emphasise parent perception of child weight status as a critical lynchpin in the childhood obesity epidemic. Intervention efforts must continue to educate parents on healthy weight development strategies.